The Impact of Visualization on Student’s Achievement in learning English language in Primary School - Zhetpisbayeva, B.A.; Shelestova, T.Y. (Ye.A.Buketov Karaganda State University Publishing house, 2019)
Student’s books are the most important teaching and learning materials. This qualitative study aims to investigate the effect of illustrations and simulation in English Course Books in a Kazakhstani context on primary school students' English language achievement by means of self-developed teaching aids («Dictionary in pictures for primary school», «Grammar in pictures for primary school», «Alphabet and spelling in pictures for primary school»). The literature review showed that simulation and illustrations play a role in primary school students’ perceptions of classroom activities (i.e., motivation, interest, challenge and joy). It was also hypothesized that simulation and illustrations affect English language achievement. To do so, the study utilized an experimental design consisting of 116 participants (58 learners in the control group and 58 students in the experimental group). The results demonstrated the positive role of simulation and illustrations in students’ language achievement. An interview was also held with a number of teachers to investigate their attitude towards self- developed teaching aids.
Ағылшын тілін оқыту барысында бастауыш сынып оқушыларының жетістігіне визуализация əдісінің беретін əсері
Влияние метода наглядности на достижения учащихся при изучении английского языка в начальной школе
Keywords: primary school; early teaching; english language; visualization; pedagogical experiment; language achievement